FORMI: Integrating Adaptive Fragmented Objects into Java RMI - Kapitza, Rüdiger; et al. (IEEE Distributed Systems Online, 2006)
FORMI integrates fragmented objects into Java RMI without requiring internal modifications to the RMI runtime and can dynamically adapt themselves by replacing existing fragments. Each FORMI object fragment internally consists of multiple components and changes the RMI architecture's stub-skeleton and reference layers. The FORMI infrastructure supports dynamic reconfiguration and adaptation of fragmented objects by providing a mechanism for replacing the fragment implementation at runtime. It's simple dictionary service demonstrates its self-adaptation features, which provides a remotely accessible dictionary with a get and a set method at some nodes. This approach is convenient for small user groups, which can provide an extended client-side fragment for stream sharing within a local network. Further development to extend the developer support and enhancing the FORMI compiler to generate glue code for fault tolerance are being planned.
UnivIS-Import:2015-04-14:Pub.2006.tech.IMMD.IMMD4.formii